Exercise capacity in single-ventricle patients after Fontan correlates with haemodynamic energy loss in TCPC. Issue 2 (2nd September 2014) - Khiabani, Reza H; Whitehead, Kevin K; Han, David; Restrepo, Maria; Tang, Elaine; Bethel, James; Paridon, Stephen M; Fogel, Mark A; Yoganathan, Ajit P
Abstract : Objective: Elevated energy loss in the total cavopulmonary connection (TCPC) is hypothesised to have a detrimental effect on clinical outcomes in single-ventricle physiology, which may be magnified with exercise. This study investigates the relationship between TCPC haemodynamic energy dissipation and exercise performance in single-ventricle patients. Methods: Thirty consecutive Fontan patients with TCPC and standard metabolic exercise testing were included. Specific anatomies and flow rates at rest and exercise were obtained from cardiac MR (CMR) and phase-encoded velocity mapping. Exercise CMR images were acquired immediately following supine lower limb exercise using a CMR-compatible cycle ergometer. Computational fluid dynamics simulations were performed to determine power loss of the TCPC anatomies using in vivo anatomies and measured flows. Results: A significant negative linear correlation was observed between indexed power loss at exercise and (a) minute oxygen consumption (r=−0.60, p<0.0005) and (b) work (r=−0.62, p<0.0005) at anaerobic threshold. As cardiac output increased during exercise, indexed power loss increased in an exponential fashion (y=0.9671x 3.0263, p<0.0001). Conclusions: This is the first study to demonstrate the relationship between power loss and exercise performance with the TCPC being one of the few modifiable factors to allow for improved quality of life. These results suggest that aerobic exercise tolerance in Fontan patients may, in part, be a consequence of TCPC power loss.